Causation and laws of nature in early modern philosophy - Ott, Walter R. (Oxford : Oxford University Press, 2009)
This is a study of one of the most important debates in 17th- and 18th-century philosophy: the nature of causation. Ott offers controversial readings of such canonical figures as Descartes, Locke, and Hume, and explores related topics such as intentionality, necessity, and relations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Causation; Philosophy of nature; Necessity (Philosophy); Natural law